Cyclophilin A modulates the sensitivity of HIV-1 to host restriction factors - Towers, Greg J; Hatziioannou, Theodora; Cowan, Simone; Goff, Stephen P; Luban, Jeremy; Bieniasz, Paul D (Nature medicine, 2003)
Many mammalian species express restriction factors that confer host resistance to retroviral infection. Here we show that HIV-1 sensitivity to restriction factors is modulated by cyclophilin A (CypA), a host cell protein that binds the HIV-1 capsid protein (CA). In certain nonhuman primate cells, the CA–CypA interaction is essential for restriction: HIV-1 infectivity is increased >100-fold by cyclosporin A (CsA), a competitive inhibitor of the interaction, or by an HIV-1 CA mutation that disrupts CypA binding. Conversely, disruption of CA–CypA interaction in human cells reveals that CypA protects HIV-1 from the Ref-1 restriction factor. These findings suggest that HIV-1 has co-opted a host cell protein to counteract restriction factors expressed by human cells and that this adaptation can confer sensitivity to restriction in unnatural hosts. Manipulation of HIV-1 CA recognition by restriction factors promises to advance animal models and new therapeutic strategies for HIV-1 and AIDS.